Museum educators and the social markers of difference: race, class and from a decolonial and sociomuseological perspective (Cadernos de Sociomuseologia, 2025)
The present text aims to reflect on some social markers of difference evidenced in interviews with educators. Data that composed the thesis 'Museum Education and Feminisms in Brazil: silences, estrangements and dialogues from an intersectional and decolonial look', defended in the Museology department of Lusófona University in 2023. Here we will address the markers related to colour/race and class. The methodology used was online semi-structured interviews and content analysis to work through the answers. The topics of markers that we will present show how professionals go through complex and confusing issues regarding their own colour/race. The class marker, on the other hand, is challenging to analyse because it is so subtle. These are important debates to be held from the perspective of decoloniality and Sociomuseology, as I explore throughout the text. Once I seek to break the barriers of coloniality by showing the powerful speeches of the educators, urgent to be heard. Museology and many museums are not interested in overcoming issues related to racism and class prejudice that generate inequalities in our society, and it is through Sociomuseology that an initial debate can be held.Keywords: 1. Social markers; 2. Color/race; 3. Class; 4. Decoloniality; 5. Sociomuseology